Crystal structure of (1α,8α,9β,12β)-1,8-diphenyl-13-oxatetracyclo-[6.4.1.0 2,7.09,12]trideca-2,4,6,10-tetraene, C24H 18O - Amarasekara, A.S. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures